Study on the Ways of Art Design Helping Rural Revitalisation-Taking Fuxiyan Village of Baihe Town, Fang County as an Example - Ding, Yan (Transactions on Social Science, Education and Humanities Research, 2024)
This study aims to explore the role and ways of art design in rural revitalisation. Taking Fuxiyan Village in Baihe Township, Fang County as an example, this study conducts an in-depth analysis of the art design projects carried out in this village, and sums up the experiences and insights of art design in helping rural revitalisation. Located in Fang County, Hubei Province, Fuxiyan Village is a typical mountainous rural area. In recent years, the village has actively responded to the strategy of rural revitalisation, and has made use of artistic design to carry out a series of renovation and upgrading of the village, which has achieved remarkable results. By analysing the art design project in Fuxiyan Village, this study finds that art design plays the following multifaceted roles in rural revitalisation. Firstly, art design improves the environmental quality of the village and enhances the aesthetic value of the village. Through landscape design and architectural renovation, Fuxiyan Village has made the village environment more livable and aesthetically pleasing, enhanced the villagers’ sense of well-being and belonging, and attracted more tourists to visit and experience the village. Secondly, artistic design promotes the inheritance and innovation of village culture. Through the art design project, Fuxiyan Village has explored and displayed the unique cultural resources of the countryside and enhanced the attractiveness of rural culture. At the same time, art design also stimulates the innovation and vitality of village culture, and promotes the integration of traditional culture and modern design. Again, art design stimulates the development potential of village economy. Fuxiyan Village has developed a series of art design-led rural tourism and cultural creative products through the art design project, which provides a new impetus and direction for the development of rural economy. Finally, art design promotes the harmonious development of rural society. The art design project in Fuxiyan Village guides villagers’ participation and collaboration, enhances villagers’ cohesion and sense of community, and promotes the harmonious development of rural society. Art design plays an important role in rural revitalisation and can be used as an effective means to improve the rural environment, pass on and innovate rural culture, and promote rural economic development and social harmony. Therefore, it is recommended to give full play to the role of art design in the process of rural revitalisation, and to realise the comprehensive revitalisation and sustainable development of the countryside through the implementation of art design projects. At the same time, attention also needs to be paid to the sustainability and social benefits of art design projects to ensure their long-term development and positive impact on rural society.